Reorientasi Fatwa Dewan Syariah Nasional (DSN-MUI) - Tamam, Ahmad Badrut (Proceedings of Annual Conference for Muslim Scholars, 2025)
The purpose of this paper is to examine the possibilities of incorporating local knowledge, local culture and traditions, and norms, into the Indonesian National Sharia Council (DSN-MUI) fatwa making process. This study aims to assess the legal structure of the fatwas issued by DSN-MUI and examine the possibilities for them to be realigned within the socio-cultural setting of Indonesia. This research employed qualitative research with a normative-juridical approach combined with doctrinal analysis on the fatwas and socio-legal analysis to contextualize their applicability within Indonesian social reality. It analyzed the DSN-MUI fatwas particularly on Islamic economic transactions, local wisdom, and the legal doctrine of ‘urf as a source of Islamic law. The research results showed the DSN-MUI fatwas has been valuable for Islamic finance industry, yet, the need for further reorientation on the stated fatwas is necessary. The research result should be re-embedded, in legal construction, and community level applicability discussed on the need for the re-interpretation of the sources of Islamic law to institute wisdom of the community to be embraced in economic product. This paper argues the need for further integration to enhance Islamic economic law to be more contextual and localized. This integration, he argues, would be ultimately necessary